Child diarrhea in Cambodia: A descriptive analysis of temporal and geospatial trends and logistic regression-based examination of factors associated with diarrhea in children under five years. - Samnang Um; Channnarong Phan; Sok Sakha; Leng Dany (PLoS ONE)
Diarrhea is a global public health problem that is the third leading cause of death in under five years, with an estimated 1.7 billion cases in 2023 and 1.8 million deaths from diarrhea diseases every year. To better understand child diarrhea in Cambodia, we examined to describe temporal and geospatial trends of diarrhea and used multiple logistic regression to analyze its association with individual and household characteristics and diarrhea among children aged 0-59 months using combined data from the Cambodia Demographic and Health Survey for 2005 to 2022. This study included 29,742 weighted children aged 0-59 months; there were 7,220 in 2005, 7,758 in 2010, 7,010 in 2014, and 7,754 in 2022, respectively. The prevalence of diarrhea among children aged 0-59 months decreased from 19.7% in 2005 to 6.2% in 2022. The highest prevalence of childhood diarrhea was observed in Kampong Cham (30.1%), in Mondul Kiri/Ratanak Kiri (24.6%), Battambang/Pailin (20.9%), and Mondul Kiri/Ratanak Kiri (12.9%) for the years 2005, 2010, 2014 and 2022. After adjusting for other variables, factors independently associated with a protective effect against childhood diarrhea included mothers aged 25-34 years (adjusted odds ratio (AOR) = 0.68; 95% CI: 0.48-0.96), 35-49 years (AOR = 0.60; 95% CI: 0.42-0.87), completed higher education (AOR = 0.61; 95% CI: 0.41-0.91), and employed (AOR = 0.79; 95% CI: 0.72-0.96). Children were less likely to have diarrhea if they were older than 36 months, belonged to the richest households (AOR = 0.69; 95% CI: 0.55-0.86), or lived in coastal region (AOR = 0.53; 95% CI: 0.41-0.69). Conversely, children born to mothers who smoke had increased odds of diarrhea (AOR = 1.61; 95% CI: 1.25-2.08), had barrier access to healthcare services (AOR = 1.20; 95% CI: 1.07-1.35), or children aged 6-23 months. Diarrhea remains highly prevalent among children in Cambodia. Public health interventions and policies to alleviate diarrhea should be prioritized to address these factors across geographical.